2008
DOI: 10.1038/mt.2008.198
|View full text |Cite|
|
Sign up to set email alerts
|

Gene Therapy for Diabetes: Metabolic Effects of Helper-dependent Adenoviral Exendin 4 Expression in a Diet-induced Obesity Mouse Model

Abstract: Exendin 4 (Ex4) is a glucagon-like peptide-1 receptor (GLP- 1R) agonist which is available as a short-acting injectable treatment for type 2 diabetes. Our aim was to characterize the long-term effects of elevated steady-state levels of Ex4 provided by in vivo gene therapy. We constructed a helper-dependent adenoviral (HDAd) vector for long-term expression of Ex4 in vivo. A high-fat diet (HFD)-induced obesity (DIO) mouse model was chosen to approximate the metabolic derangements seen in obese patients. Mice wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 50 publications
4
44
1
Order By: Relevance
“…Here we demonstrate the unequivocal development of hepatic fibrosis in the absence of circulating leptin and expand on the previously reported beneficial effect of GLP-1R agonism on body weight, liver size, and liver lipid (10,31) by demonstrating a potential benefit of GLP-1R agonism on fibrosis (assessed both histologically and biochemically). We also demonstrate that benefits of GLP-1R agonism on NAFLD/ NASH are largely, but not entirely, accounted for by weight loss.…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…Here we demonstrate the unequivocal development of hepatic fibrosis in the absence of circulating leptin and expand on the previously reported beneficial effect of GLP-1R agonism on body weight, liver size, and liver lipid (10,31) by demonstrating a potential benefit of GLP-1R agonism on fibrosis (assessed both histologically and biochemically). We also demonstrate that benefits of GLP-1R agonism on NAFLD/ NASH are largely, but not entirely, accounted for by weight loss.…”
mentioning
confidence: 85%
“…Functional GLP-1R has been localized on primary rat hepatocytes, immortalized mouse liver cell lines, and human hepatocytes (10,13). GLP-1R agonism has been associated with reduced hepatic lipogenesis and enhanced fat oxidation in rodents (5,10,31,37). More recently, a role for GLP-1R agonism in the regulation of endoplasmic reticulum (ER) stress and the unfolded protein response has emerged.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one study, mice fed a high-energy diet for 23 weeks and then treated with pioglitazone for an additional 8 weeks exhibited normal insulin sensitivity at the end of the study but showed no improvement in hepatic steatosis or serum ALT (17). By contrast, mice fed a high-energy diet for 8 weeks and then treated with an adenovirus expressing exendin-4 (a long-acting agonist of glucagon-like peptide receptor-1) while continuing the diet for 15 more weeks showed improvements in both glucose utilization and hepatic steatosis (106). Anti-inflammatory drugs have also been used to reduce insulin resistance in the setting of high-energy feeding, based on evidence that insulin resistance is the consequence of a diet-induced pro-inflammatory state (11).…”
Section: Obesity and Systemic Insulin Resistancementioning
confidence: 99%
“…Delivery methods are divided into viral [19,21] and non-viral [17] methods. the latter includes those using liposomes [3,16,21], nanoparticles [23], and a hydrodynamic method [2].…”
Section: Introductionmentioning
confidence: 99%